UNDERSTANDING OF THE CONCEPT OF FRICTION IN THE EQUILIBRIUM DIRECTION OF LEARNING USING VISUAL MEDIA IN CLASS XI MIA-I SMA NEGERI 4 PALANGKA RAYA ACADEMIC YEAR 2017/2018 - Mia Pesie (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2018)
The purpose of this study was to describe the understanding of the concept of shifting the equilibrium direction of the results of learning using visual media in class XI MIA-I SMA Negeri 4 Palangka Raya 2017/2018 Academic Year. This study involved 22 students of class XI MIA-I Palangka Raya who had not received the subject matter of the factors that influence the shift in the direction of bequilibrium. The instrument used was a form of learning and student learningf activities, student response questionnaires, and concept comprehension tests (Pretest and Posttest). The data obtained were then analyzed descriptively to see the understanding of the concepts from the media used. The results of research and data analysis have been done that the average percentage of learning outcomes using visual media is carried out with very good categories, the implementation of learning using visual media is in a very good category, learning activities of group of students with excellent categories and understanding of students concepts after using visual media on indicator 1 is 100%, on indicator 2 is 95,45%, on indicator 3 is 74,24% and on indicator 4 is 72,72%. Based on these results it was concluded that using visual media was able to improve students conceptual understanding of the sub topics of the factors that influence the direction of equilibrium.